Estudos de validação e normatização do Teste de Memória (MEMO) - Feitosa, Julia Akel de Oliveira (Brasil, 2024)
This study conducted an in-depth investigation into the internal structure validity and criterion validity of the Memory Test (MEMO), while also establishing norms for its application. The MEMO is a psychometric instrument used to assess memory functions. This research utilised a documentary and quantitative design, drawing from a database containing 873 response protocols from participants aged 6 to 75 years, gathered from empirical studies conducted between 2017 and 2023. Evidence of internal structure validity was obtained through principal component analysis, which confirmed the multi-component structure of the test. Criterion validity was examined through the correlation of MEMO performance with related measures, demonstrating a significant association. Finally, norms for MEMO application were established based on a representative sample of the population, providing parameters for the interpretation of test results. The results suggest that MEMO is a robust and reliable tool for memory assessment, supporting its applicability in clinical and research settings.